The etiologies of adrenal insufficiency in 73 Thai children: 20 Years experience - Prapanrat Osuwannaratana (2018)
Background: Adrenal insufficiency (AI) is an event caused by an inadequate secretion or action of adrenal hormones. It can be classified as primary (1°) and secondary (2°). AI may result in severe morbidity and mortality when undiagnosed or ineffectively treated. Objective: To determine the etiologies of AI in Thai children Material and Method: Data of children with AI presented to the authors' pediatric endocrine service between 1982 and 2002 (20 years) were retrospectively collected and analyzed. Results: AI was diagnosed by clinical and laboratory data in 73 children (31 boys and 42 girls). Sixty-two (84.9%) patients had 1° AI while 11 (15.1%) had 2° AI. The majority of patients with 1° AI (87.1%) were diagnosed with congenital adrenal hyperplasia (CAH). Other causes of 1° AI were uncommon such as ACTH unresponsiveness (4.8%) and no definite diagnosis (8.1%). Most children with 1° AI presented with hyperpigmentation. Causes of 2° AI were as follows: panhypopituitarism (63.6%), isolated ACTH deficiency (9.1%), and low birth weight (27.3%). Conclusion: In the present study, CAH was the most common cause of 1° AI while panhypopituitarism was the most common cause of 2° AI. Other causes of AI were quite uncommon. Definite causes of AI have not yet been identified in some children. Further clinical observation and special tests including molecular studies in these children are warranted for diagnostic and prognostic importance.